Tenun Songket Kampung Wisata Tenun Khatulistiwa Kota Pontianak - Arkanudin, Arkanudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research aims to describe sogket weaving in equatorial weaving tourism village. The existence of this village began to be widely known after it was inaugurated by the Mayor of Pontianak in 2018. The research method was descriptive qualitative research. Data collection techniques include interviews, observations, and literature searches. The results showed that weavers in this village still produce songket motifs and patterns typical of Pontianak Malay, but Sambas characteristics dominate even though they use gill motif fabrics. The patterns and textures are also innovations of new creations from the craftsmen themselves. The new motif, which is a weaver s creation, does not yet have a name like a typical Pontianak Malay motif or a typical Sambas songket weaving cloth.